2014
DOI: 10.1042/bj20131198
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase inhibitor β enhances the constitutive activity of G-protein-coupled zinc receptor GPR39

Abstract: GPR39 is a G-protein-coupled zinc receptor that protects against diverse effectors of cell death. Its protective activity is mediated via constitutive activation of Gα13 and the RhoA pathway, leading to increased SRE (serum-response element)-dependent transcription; the zinc-dependent immediate activation of GPR39 involves Gq-mediated increases in cytosolic Ca2+ and Gs coupling leading to increased cAMP levels. We used the cytosolic and soluble C-terminus of GPR39 in a Y2H (yeast-2-hybrid) screen for interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…If the width of the histogram that gives the distribution of periods from the bootstrap calculation is narrow, the uncertainty in the derived period is low. For the sources that pass the above tests, we fit the light curves with a Fourier series (Kovacs & Kupi 2007). The Fourier parameters are similar to the light curves of classical Cepheids for P ∼ 3 − 15 days observed in the K-band (Persson et al 2004;Bhardwaj et al 2015).…”
Section: Results and Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…If the width of the histogram that gives the distribution of periods from the bootstrap calculation is narrow, the uncertainty in the derived period is low. For the sources that pass the above tests, we fit the light curves with a Fourier series (Kovacs & Kupi 2007). The Fourier parameters are similar to the light curves of classical Cepheids for P ∼ 3 − 15 days observed in the K-band (Persson et al 2004;Bhardwaj et al 2015).…”
Section: Results and Analysismentioning
confidence: 94%
“…To ensure that the shapes of the light curves are quantitatively similar to classical Cepheids, we compute their Fourier parameters, as well as the skewness and acuteness parameter, and visually inspect all the light curves. We have computed the Fourier parameters of our sources (Figure 3), following Kovacs & Kupi (2007). Out to fourth-order the Fourier series is expressed as:…”
Section: Results and Analysismentioning
confidence: 99%
“…Another receptor that interacts with zinc is the zinc-specific receptor/G protein-linked receptor 39 (mZnR/GPR39) [163][164][165]. This receptor is expressed in cerebral areas such as cortex, amygdala or hippocampus [166], and, upon its activation by zinc, it triggers an increase in Ca+2 release and consequently the activation of a series of intracellular signaling pathways [167].…”
Section: Zinc Signalingmentioning
confidence: 99%
“…10 To date, studies have found that PKIB has the ability to enhance the constitutive activity of the G-protein-coupled zinc receptor GPR39 and may play important roles in vascular endothelial cells. 11,12 Furthermore, there are a few studies about the functions of PKIB in the tumor progression process. In breast cancers, PKIB expression is strongly correlated with the triplenegative breast cancer subtype, and overexpression of PKIB promotes tumor aggressiveness in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%